TESTICULAR DEVELOPMENT AND SEMINAL ATTRIBUTES OF AGONDA GOAN PIG - CHAKURKAR, EB; NAYAKVADI, S; NAIK, PK; MANDAL, A; KARUNAKARAN, M (The Indian Journal of Animal Reproduction, 2022)
Out of thirty-six male Agonda Goan pigs (age, 30-270 d), six males were castrated at a time in a 30 d interval starting from 30 d to 180 d to study the biometry of testis and epididymis, whereas, six males were left uncastrated for semen studies. Testicular length, width, thickness, circumference, weight and epididymal weight were increased (p<0.05) from 30 to 180 d age. Motile sperms were found in cauda epididymis at 60 d age. Sperm cells harvested at 180 d showed maturity (p<0.05). The average volume of semen ejaculate (87.3±30 ml), sperm cell concentration (136.8x106 /ml) and mean total sperm cells per ejaculate (10.79 x 106) in Agonda Goan pigs were comparatively lower than reported values of exotic pigs, while testosterone level were higher than the exotic pigs at similar age.